Learners’ perception towards dubbing on oral language learning: a systematic review (2017-2023) - Qiuyao, Wang; Noordin, Nooreen; Jeyaraj, Joanna Joseph; Zhao, Sun (Human Resources Management Academic Research Society (HRMARS), 2024)
In recent years, dubbing has increasingly been used in second or foreign language learning. As learners’ perceptions are relevant to the achievement of their learning, this research study aims to investigate learners’ perceptions towards the application of dubbing to second language learning and teaching with a focus on spoken language acquisition from 2017 to 2023. Out of the total of 15,997 articles initially searched, only 22 were ultimately included in the analysis. The results suggest that (1) intralingual dubbing occupied the largest proportion in terms of the types of dubbing adopted in the included studies (2) there is an increasing research trend on the effect of students of identified levels (3) questionnaire secures its reputation in collecting data in terms of learners’ perceptions (4) A majority of students maintain a favourable attitude towards it, as it is believed effective, interesting, entertaining, and helpful to improve their ICT skills, creativity and motivation (5) The complaints about dubbing mainly focus on the long time and hard work invested(6) Most complaints related to aspects beyond dubbing, for example, technical problems (7) Peer pressure can serve as both a source of motivation and demotivation for students while students share their dubbing works.